The Relationship between the Improvement Level in Blood Gas Parameters in Time and Brain MRI Findings in Newborns with the Diagnosis of Hypoxic Ischemic Encephalopathy - Aslan Yilmaz; Abdulkerim Uygur; Barıs Celik; Ali Metin Akdag; Demet Baser; Sureyya Ipek Ozturk (AVES Yayincilik, 2024)
Objective: In this study, we aimed to evaluate the relationship between the level of improvement in blood gas parameters in the first hours of age and normal and diffusion-restriction brain magnetic resonance imaging (MRI). Materials and Methods: The study is a retrospective cohort study. Cases of the diagnosis of hypoxic-ischemic encephalopathy (HIE) who received therapeutic hypothermia in our unit between January 2022 and January 2024 were included in the study. Clinical findings, blood gas values (first, cord; second, first hours of age; third, 24th hour of age), and MRI results were recorded from the case files and compared between normal and diffusion-restricted brain MRI groups. Results: Diffusion-restricted brain MRI was detected in 10 out of a total of 19 cases. The 5-minute Apgar score was lower (p=0.038) and mechanical ventilator support was higher (P=.003) in the diffusion-restricted MRI group than in the normal MRI group. The relationship was shown between high base excess (P=.022) in cord blood gas, low HCO₃ (p=0.025) in the 24th hour blood gas, and convulsion (P=.033) in the diffusion-restricted MRI group. Additionally, it was found that only the improvement level of the pH value in the first hour of age was significant (P=.025) in the diffusion-restricted brain MRI group than in the normal MRI group. Conclusion: We showed that there was a relationship between diffusion-restricted brain MRI and the improvement level in the pH value in the first hours of age of patients diagnosed with HIE who received treatment for therapeutic hypothermia.